Media Sosial Instagram Sebagai Sarana Promosi Untuk Meningkatkan Penjualan Krispy Yammy Babeh - Ramadhan, Hikmah; Gunawan, Ce; Taslim, Muhammad (Institut Manajemen Wiyata Indonesia, 2020)
This study aims to analyze the effect of sales promotion and direct marketing on the sales volume of Yammy Babeh's cassava chips products. The research method used is a quantitative method with associative research type. Respondents consisted of 100 people who followed Krispy Yammy Babeh's Instagram account, had made purchases, and were fully willing to be involved in the research process. Based on the findings, analysis and discussion, it can be concluded that both partially and simultaneously there is a significant influence between the independent variables, namely sales promotion (X1) and direct marketing (X2) through social media Instagram on the dependent variable, namely Sales Volume (Y). Sales promotion activities to introduce products can be carried out massively and continuously to make it easier for customers or potential customers to know more details about the products being sold. Yammy Babeh's online direct marketing activities in all online media, including Instagram, are able to attract consumers to make purchases.